Green Synthesis of Copper Nanoparticles using Zingiber officinale Extract and Characterization - Oli, Hari Bhakta; Sharma, Nabin; KC, Ekaraj; Subedee, Anup; Timilsina, Rajan (Journal of Nepal Chemical Society, 2018)
Available with full text.